2015
DOI: 10.5812/aapm.20350
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of the Iranian Version of the Quality of Recovery-40 Questionnaire

Abstract: Background:Recovery after anesthesia and surgery is a complex process and depends on many factors such as patient, anesthesia and surgery conditions as well pre-existing comorbidities.Objectives:The aims of this study were to translate the 40-item quality of recovery score (QoR-40) into Persian and evaluate its psychometric properties in Iranian patients.Patients and Methods:We enrolled patients candidate for elective general surgery undergoing general anesthesia from July 2013 to December 2013 at Shahid Rajae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
2
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 36 publications
5
17
2
8
Order By: Relevance
“…This may be because El-Demerdash hospital is a governmental educational hospital that provides treatment with low cost and most of patients who receive treatment in this hospital are from low socio-economic standard who live mainly in rural areas. These results are contradicted with Yaghoobi et al, (2015) [16] who stated that nearly three quarters of patients were from urban areas, while one quarter from rural, and the mean of BMI of patients was 27.14 ± 15.56.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This may be because El-Demerdash hospital is a governmental educational hospital that provides treatment with low cost and most of patients who receive treatment in this hospital are from low socio-economic standard who live mainly in rural areas. These results are contradicted with Yaghoobi et al, (2015) [16] who stated that nearly three quarters of patients were from urban areas, while one quarter from rural, and the mean of BMI of patients was 27.14 ± 15.56.…”
Section: Discussioncontrasting
confidence: 56%
“…This result is in accordance with Berg, Kjellgren, Unosson, & Årestedt, (2012) [18] who stated that more than two thirds of patients were employed, but is contradicted with Yaghoobi et al, (2015) [16] who mentioned that more than half of patients under study were divorced or widowed. The results revealed that half of patients were educated (21% secondary, 29% bachelor), while the others were illiterate or read and write.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Nonetheless, measurements obtained from the patients' records are vital for appropriate monitoring of this period. (3) Several assessment instruments of postoperative recovery have been developed. Among these, the Quality of Recovery-40 Item (QoR-40) stands out, because it is widely indicated for this purpose, presents good results regarding its psychometric properties, is the most commonly used in clinical trials and has been translated into several languages.…”
Section: Introductionmentioning
confidence: 99%